Effects of Additions of Monascus and Laccaic acid on the Color and Quality Properties of Nitrite-Free Emulsion Sausage during Refrigerated Storage - Seong, Pil-Nam (Korean J Food Sci Anim Resour, 2017)
This effect of Monascus and Laccaic acid on the chemical composition, physical, texture and sensory properties of sausage were investigated during storage. Eight treatments (T) of sausage such as T1 (12 ppm sodium nitrite), while T2, T3, T4, T5, T6 and T7 were formulated with different ratios of Monascus/Laccaic acid: 63/7.0, 108/12, 135/15, 59.5/10.5, 102/18 and 127.5/22.5 ppm, respectively. The batch formulated without nitrite or Monascus and laccaic acid was served as control (C). The control sausages had higher pH values compared to the treated ones at 3, 10 and 28 d storage (p<0.05). After 10 d storage, the pH values decreased in treated sausage samples (p<0.05). The T1 and T4 presented the lowest yellowness and lightness values, respectively over the storage period. The redness values were increased as increasing Monascus and Laccaic acid amounts (T2-T4, T5-T7). The addition of Monascus and Laccaic acid had significantly higher hardness and springiness values (p<0.05) compared with the control in 3, 19 or 28 d storage. The results indicated that the addition of Monascus and Laccaic acid could improve the redness of the products.